Can overharvesting of a non-timber-forest-product change the regeneration dynamics of a tropical rainforest? The case study of Euterpe edulis - Muler, Ana Elena; Rother, Débora C.; Brancalion, Pedro S.; Naves, Rafaela P.; Rodrigues, Ricardo R.; Pizo, Marco A. (Elsevier, 2013)
The exploitation of non-timber forest products is often considered a low-impact activity in tropical forests. However, assessments of the impacts of such activity are mostly focused on the harvested species and not on the plant community, thus limiting our understanding for establishing forest management recommendations. We investigated the consequences of Euterpe edulis palm heart harvesting on the seed rain in the Brazilian Atlantic rainforest. We compared the density of E. edulis individuals, as well as the density of E. edulis seeds, and the density, richness and functional composition of seed rain of the whole plant community, before and after palm heart harvesting in a 10 ha permanent plot. This assessment was carried out in preserved (typical old-growth Atlantic rainforest) and in disturbed (more open habitat dominated by the native bamboo Guadua tagoara) forest patches. Palm harvesting reduced the E. edulis population from 202.16 to 25.67 ind/ha and its seed rain density from 0.362 to 0.3 seeds/m2 and from 2.395 to 0.15 seeds/m2 in preserved and disturbed forest patches, respectively. Seed density of light-dependent climbers, pioneer trees, bamboo and animal-dispersed seeds increased after palm harvesting, especially in the disturbed forest patches, where palm harvesting was more intense and may have changed the light regime of the understory. On the other hand, species richness of the plant community declined by half. We observed a remarkable decline in the number of animal-dispersed species, especially for those with large seeds, suggesting that the activity of seed dispersers, including many species attracted by E. edulis fruits, was reduced. Therefore, harvesting of E. edulis palm heart may change the regeneration dynamics of the Atlantic rainforest, both due to shifts in forest structure, mediated by the removal of individuals from the forest canopy, and in community functioning, mediated by the interference on the activity of seed dispersers. © 2013 Elsevier B.V. All rights reserved.
Keywords: Forest succession; Harvesting; Keystone species; Seed dispersal; Seed rain